Hairpin DNAzymes: a new tool for efficient cellular gene silencing. - Abdelgany, A; Wood, M; Beeson, D (2007)
BACKGROUND: RNA-based gene silencing is potentially a powerful therapeutic strategy. Catalytic 10-23 DNAzymes bind to target RNA by complimentary sequence arms on a Watson-Crick basis and thus can be targeted to effectively cleave specific mRNA species. However, for in vivo applications it is necessary to stabilise DNAzymes against nucleolytic attack. Chemical modifications can be introduced into the binding arms to increase stability but these may alter catalytic activity and in some cases increase cell toxicity. METHODS: We designed novel 10-23 DNAzyme structures that incorporate stem-loop hairpins at either end on the DNAzyme binding arms. The catalytic activity of hairpin DNAzymes (hpDNAzyme) were tested in vitro against 32P-labelled cRNA encoding the muscle acetylcholine receptor (AChR) alpha-subunit. Resistance of hpDNAzymes to nucleolytic degradation was tested by incubation of the hpDNAzymes with Bal-31, DNase1 or HeLa cell extract. Gene silencing by hpDNAzymes was assessed by measuring reduced fluorescence from DsRed2 and EGFP reporters in cell culture systems, and reduced 125I-alpha-bungarotoxin binding in cells transfected with cDNA encoding the AChR. RESULTS: We show that hpDNAzymes show remarkable resistance to nucleolytic degradation, and demonstrate that in cell culture systems the hpDNAzymes are far more effective than standard 10-23 DNAzymes in down-regulating protein expression from target mRNA species. CONCLUSION: hpDNAzymes provide new molecular tools that, without chemical modification, give highly efficient gene silencing in cells, and may have potential therapeutic applications.